Health and Disability: Partnerships in Health care. Issue 1 (January 2015) - Tracy, Jane; McDonald, Rachael
<x xml:space="preserve">Abstract</x> Background Despite awareness of the health inequalities experienced by people with intellectual disability, their health status remains poor. Inequalities in health outcomes are manifest in higher morbidity and rates of premature death. Contributing factors include the barriers encountered in accessing and receiving high‐quality health care. Aims This paper outlines health inequalities experienced by people with intellectual disability and focuses on the opportunities medical education provides to address these. Strategies to ensure that health professional education is inclusive of and relevant to people with disabilities are highlighted. Conclusions The barriers experienced by people with intellectual disabilities to the receipt of high‐quality health care include the attitudes, knowledge and skills of doctors. Improving medical education to ensure doctors are better equipped is one strategy to address these barriers. Improving health enhances quality of life, enables engagement and optimizes opportunities to participate in and contribute to the social and economic life of communities. Accessible Abstract People with intellectual disabilities sometimes find it difficult to get the healthcare they need to stay well. Teaching student doctors about what people with disabilities want and need can help these students become better doctors. Good doctors help people get well and stay healthy and active. When people feel well they can enjoy their lives and join in activities in their community. This article talks about some of the things doctors need to learn, and some ways to teach them. People with disabilities have a very important role in teaching student doctors.